The yield and quality of cassiavera (Cinnamomum burmanii L.) oil at different harvest ages from Malalak farmers in West Sumatra - Ardinal Ardinal; Salmariza Sy; Firdausni Firdausni; F Failisnur; Inda Three Anova (Jurnal Litbang Industri, 2022)
This study compared the oil yield and identified the quality of cassiavera with plants ages 7 years, 18 years, and random (broken) one. Parameters measured included yield, physicochemical properties, and chemical composition. Based on the results, the oil yield was 1%, 0.9%, and 0.7% at ages 8 and 7 years of upper and lower stem parts, as well as for the broken form. This indicates that the longer plant age correlates with a higher yield. The yield at 7 and 18 years is not much different, hence the harvest can be performed at the age of 7 years considering a shorter waiting period. The physicochemical test of oil solubility in 70% ethanol showed a ratio of 1:1 and a clear appearance according to the maximum requirements of INS (Indonesian National Standard) 06-3734:2006, namely 1:3 clear. Meanwhile, the refractive index (RI) test indicated 1.56 as the best value for cassiavera scion at the age of 7 years in line with INS 06-3734:2006 conditions of 1.559 - 1.595. The chemical composition test for the oil as a whole complied with the minimum standard of INS 06-3734:2006, namely 50% cinnamaldehyde.